New insights into enhancing maximal exercise performance through the use of a bitter tastant - Gam, S.; Guelfi, K. J.; Fournier, P. A. (Sports Medicine, 2016)
It is generally acknowledged that for an orally administered ergogenic aid to enhance exercise performance it must first be absorbed by the gastrointestinal tract before exerting its effects. Recently, however, it has been reported that some ergogenic aids can affect exercise performance without prior absorption by the gastrointestinal tract. This is best illustrated by studies that have shown that rinsing the mouth with a carbohydrate (CHO) solution, without swallowing it, significantly improves exercise performance. The ergogenic effects of CHO mouth rinsing in these studies have been attributed to the activation of the brain by afferent taste signals, but the specific mechanisms by which this brain activation translates to enhanced exercise performance have not yet been elucidated. Given the benefits of CHO mouth rinsing for exercise performance, this raises the issue of whether other types of tastants, such as bitter-tasting solutions, may also improve exercise performance. Recently, we performed a series of studies investigating whether the bitter tastant quinine can improve maximal sprint performance in competitive male cyclists, and, if so, to examine some of the possible mechanisms whereby this effect may occur. These studies have shown that mouth rinsing and ingesting a bitter-tasting quinine solution can significantly improve the performance of a maximal cycling sprint. There is also evidence that the ergogenic effect of quinine is mediated, at least in part, by an increase in autonomic nervous system activation and/or corticomotor excitability. The purpose of this article is to discuss the results and implications of these recent studies and to suggest avenues for further research, which may add to the understanding of the way the brain integrates signals from the oral cavity with motor behaviour, as well as uncover novel strategies to improve exercise performance.